2019
DOI: 10.1111/een.12764
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes over time in individual‐based networks involving a harvester ant, seeds, and invertebrates

Abstract: 1. Harvester ants perform important ecological functions, such as seed predation and redistribution of nutrients in the soil, through a complex of ecological interactions. Most studies are static descriptions of network structure, while their temporal organisations and the factors that modulate it have been neglected. 2. This study describes the temporal organisation and the influence of climatic variables (e.g. temperature and rainfall) on network structure between a harvester ant species and its food resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…Thus, some ants can change their foraging patterns according to the availability of resources in the environment (Belchior, Del‐Claro, & Oliveira, 2012; Whitford & Jackson, 2007). For instance, Anjos, Luna, Borges, Dáttilo, and Del‐Claro (2019) showed that granivorous ants can change their foraging behaviour due to the seasonality of the environment, which results in changes in resource availability (also see Donoso, Johnston, & Kaspari, 2010). Therefore, in our region we observe that biotic and abiotic factors lead to the simultaneous occurrence of EFNs, ants and herbivores, and the production of new leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some ants can change their foraging patterns according to the availability of resources in the environment (Belchior, Del‐Claro, & Oliveira, 2012; Whitford & Jackson, 2007). For instance, Anjos, Luna, Borges, Dáttilo, and Del‐Claro (2019) showed that granivorous ants can change their foraging behaviour due to the seasonality of the environment, which results in changes in resource availability (also see Donoso, Johnston, & Kaspari, 2010). Therefore, in our region we observe that biotic and abiotic factors lead to the simultaneous occurrence of EFNs, ants and herbivores, and the production of new leaves.…”
Section: Discussionmentioning
confidence: 99%
“…For example, temperatures alter daily foraging activity which can be geographically dependent (Stuble et al, 2013(Stuble et al, , 2014; however, harvester ants generally display unimodal activity in cooler months and bimodal patterns in warmer months (Crist & MacMahon, 1992;Stuble et al, 2013Stuble et al, , 2014. Vegetation structure, resource distance, and biotic factors, such as larger colonies and neighboring nests, are additional factors that can influence harvester ant foraging (Anjos et al, 2019;Gordon & Kulig, 1996;MacMahon et al, 2000). Our final objective was to evaluate the relative effects these factors had on seed removal by harvester ants.…”
Section: Introductionmentioning
confidence: 99%
“…Species are delimited by a heterogeneous distribution of resources and environmental conditions (Wang et al, 2001), which determine potential local interactions (Perfecto & Vandermeer, 1996;Camarota et al, 2016;Queiroga & Moura, 2017). For instance, some authors discuss how annual temperature and rainfall affect ants' survival and how warmer and wetter conditions can increase the diversity and frequency of ant-plant interactions (Costa et al, 2018;Anjos et al, 2019;Bujan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%